2015
DOI: 10.1128/iai.02289-14
|View full text |Cite
|
Sign up to set email alerts
|

In VivoMechanisms Involved in Enhanced Protection Utilizing an Fc Receptor-Targeted Mucosal Vaccine Platform in a Bacterial Vaccine and Challenge Model

Abstract: T he limited success of immunization against mucosal pathogens and the lack of effective and safe adjuvants highlight the urgent need for mucosal vaccines. As a result, researchers have utilized novel strategies to target antigens (Ags) to receptors expressed on the surfaces of antigen-presenting cells (APCs), such as dendritic cells (DCs) and macrophages, in an effort to more effectively activate the mucosal immune system and elicit robust and protective immune responses (1). Importantly, in this regard, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…For example, intraperitoneal injection of monoclonal antibody targeting a lipopolysaccharide of the Q fever producing facultative intracellular organism Coxiella burnetii has shown to protect mice against aerosolized infection . Also in accordance with these notions, vaccines based on the induction of antibodies that promote phagocytosis of respiratory, intracellular pathogens such as Yersinia pestis and Francisella tularemia have recently been developed and shown protection against plague and tularemia . Furthermore, alveolar macrophages and epithelial cells produce several proteins of the classical and alternative pathways of complement , and complement proteins have been detected in the bronchoalveolar lavage fluid from various different mammalian species including humans .…”
Section: Role Of Humoral Immunity At Different Stages Of Mtb Infectionmentioning
confidence: 97%
“…For example, intraperitoneal injection of monoclonal antibody targeting a lipopolysaccharide of the Q fever producing facultative intracellular organism Coxiella burnetii has shown to protect mice against aerosolized infection . Also in accordance with these notions, vaccines based on the induction of antibodies that promote phagocytosis of respiratory, intracellular pathogens such as Yersinia pestis and Francisella tularemia have recently been developed and shown protection against plague and tularemia . Furthermore, alveolar macrophages and epithelial cells produce several proteins of the classical and alternative pathways of complement , and complement proteins have been detected in the bronchoalveolar lavage fluid from various different mammalian species including humans .…”
Section: Role Of Humoral Immunity At Different Stages Of Mtb Infectionmentioning
confidence: 97%
“…Previous experiments have shown that co-culturing of Ft - specific T cell hybridoma with mouse PECs in the presence of mAb-i Ft noticeably increased Ft -specific T cell responses compared to using the i Ft immunogen alone [ 26 ]. In addition, in vivo administration of mAb-i Ft ICs intranasally increased the activation status of mucosal dendritic cells in the lungs of immunized mice [ 25 ]. Therefore, we hypothesized that targeting of immunogen to Fcγ receptors (FcγRs) increases systemically the activation status of antigen presenting cells following LVS challenge.…”
Section: Resultsmentioning
confidence: 99%
“…tularensis -specific cytokine and antibody responses, (4) generation of effector memory CD4 + T cells, and (5) increased protection against F . tularensis infection [ 19 , 25 , 26 ]. In the current study we hypothesized that F .…”
Section: Introductionmentioning
confidence: 99%
“…For example, intraperitoneal injection of monoclonal antibody targeting a lipopolysaccharide of the Q fever producing facultative intracellular organism Coxiella burnetii has shown to protect mice against aerosolized infection (36). Also in accordance with these notions, vaccines based on the induction of antibodies that promote phagocytosis of respiratory, intracellular pathogens such as Yersinia pestis and Francisella tularemia have recently been developed and shown protection against plague and tularemia (28,29,122). Furthermore, alveolar macrophages and epithelial cells produce several proteins of the classical and alternative pathways of complement (123,124), and complement proteins have been detected in the bronchoalveolar lavage fluid from various different mammalian species including humans (125)(126)(127)(128).…”
Section: Role Of Humoral Immunity In Preventing or Rapidly Clearing Imentioning
confidence: 99%